Climate as a Mediating Influence on the Perceived Academic Success of Women Student-Athletes. Issue 3 (1st September 2016) - Hoffman, Jennifer Lee; Rankin, Susan R.; Loya, Karla I.
Abstract : Women student-athletes are often underrepresented in policy reforms aimed at improving academic outcomes among college athletes. Using data from a national survey of 8481 student-athletes in all National Collegiate Athletic Association intercollegiate divisions and sports, the effects of climate on the academic success of women student-athletes are examined. The Student-Athlete Climate Study conceptual framework is tested, then seven factors that gauge women student-athletes' perceptions of climate are measured. Indicators with most influence on academic success among women student-athletes are: faculty–student interaction, personal comfort with teammate diversity, and perceptions of respect.